THE POLICY MODEL FOR SUSTAINABLE COMMUNITY FOREST: A FACTOR ANALYSIS - Tatan Sukwika; Lidya Fransisca (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2021)
Developing and maintaining forest sustainably is a way to support sustainable development. From the technical point of view, the sustainability of community forest could be articulated not only based on the three aspects i.e. economic (ECO), social culture (SOC), ecology (EGY), but it can also include dimensions of legal & institutional (LIT), and accessibility & technology (ACT). This study aims to determine variables of sustainability dimensions that have a direct positive effect on the sustainability of the community forests (SCF), to identify variables that affect SCF and variables of sustainability dimensions that have dominant effect on SCF. This study employed 70 samples of forest farmers’ group in Bogor regency. The respondents were purposively selected based on consideration of the criteria for forest farmer groups namely beginner, intermediate, and advanced. The Analysis tools used PLS-SEM. Sustainability dimensions of ECO, EGY, LIT, and ACT have a significant positive direct effect on SCF. The mediational hypothesis testing suggested that there is a partial mediation from ECO and EGY to SCF, which is consistent and have a positive value. Based on the coefficient value of the total-effect, among the five dimensions, ecology value was the biggest and the most robust. The policy implies that the ecological aspects considered the importance and strategy. Therefore, the value and productivity of the community forest structure and composition need to be maintained.